Maximal accumulated oxygen deficit and blood responses of ammonia, lactate and pH after anaerobic test: a comparison between international and national elite karate athletes - Ravier, G.; Dugue, B.; Grappe, F.; Rouillon, J. D. (International Journal of Sports Medicine, 2006)
The purpose of this study was to compare maximal accumulated oxygen deficit (MAOD) and the time course of blood markers of the anaerobic metabolism in response to exhaustive supramaximal test in two elite (international vs. national) class karate athletes. Ten male international competitors from the French national team (Int, age 21.2 ± 3.1 years, 71.9 ± 11.4 kg) and eight national class (Nat, 23.7 ± 2.4 years, 70.7 ± 12.2 kg) athletes with a similar maximal oxygen uptake of 57.6 and 59.4 ml· kg-1 · min-1, respectively, were involved in this study. The MAOD was determined after an exhaustive supramaximal exercise (2 - 3 min at 140 % of their V·O2max velocity) on a treadmill ergometer. Blood lactate, pH and plasma ammonia were determined at rest, immediately at the end of exercise and during the recovery period at 2, 4, 6, 8, 10 and 15 min. After the supramaximal exercise, a dramatic higher increase in the blood concentration of ammonia until its peak was observed in the Nat compared with the Int. Time course of [NH4+] and [La] reveals significant (p < 0.01) differences between the two groups. Peak values for [H+] (89.2 ± 6.7 vs. 75.9 ± 8.8 nmol · l-1; p < 0.01), [NH4+] (180 ± 67.9 vs. 118.7 ± 22.7 µmol · l-1; p < 0.05) and [La] (20.7 ± 2.7 vs. 17.9 ± 1.1 mmol · l-1; p < 0.05) were higher in Nat compared with Int group, respectively. However, the MAOD was similar in both groups (67.8 ± 8 ml · kg-1 and 64.5 ± 6.4 for Int and Nat groups, respectively). These data suggest that ammonia and lactate accumulation are sensitive to the level of performance in karate. Higher concentrations of these metabolites in blood after supramaximal exhaustive exercise may be related to either higher anaerobic contribution to energy supply in Nat or higher removal ability in the Int group.